Geochemistry of Permian Kuantan granite Peninsular Malaysia: implication to highly fractionated I - type granite - Azmiah Jamil,; Azman A. Ghani,; Ahmad Farid Abu Bakar,; Mohd Rozi Umor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The 262.0 ± 1.7 Ma Kuantan granite of the Peninsular Malaysia Eastern Belt comprises coarse-grained biotite monzogranite and syenogranite. The granite marked the earliest subduction-related magmatic intrusion during the collision of the Sibumasu and Indochina blocks. This paper reported whole-rock geochemical data of Kuantan granite to constrain the magma source and petrogenesis of the granite. The Kuantan granite stands out due to its elevated SiO2 concentration, surpassing 72%. It also exhibits high levels of K2O, ranging from 4.51% to 6.5%. The A/CNK value falls between 1.01 and 1.08, and there are notable negative Eu anomalies that range from 0.05 to 0.27. Together with other older fractionated I-type granites in the easternmost Peninsular Malaysia, they formed distinct granitic facies from the eastern Belt granite proper. This study suggests that the Permian highly fractionated I-type granites resulted from the partial melting of intra-crustal mafic rocks, while the primitive I-type granitic melts underwent significant fractional crystallization.